ANALISIS KOMUNIKASI INTERPERSONAL GURU DAN SISWA DALAM PEMBELAJARAN MATEMATIKA SISWA SMP NEGERI 3 SRAGEN - Anjarsari, Dewi; Lestariningsih, Nofita; latifah, rizka (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Learning is a process of interaction between learners and their environment, so that there are changes in behavior in a better direction. The learning process is experienced throughout life and applies anywhere and anytime. This study aims to identify the analysis used by teachers in implementing mathematics learning and student involvement in understanding student communication of learning materials. This research method uses a descriptive qualitative approach with data collection techniques including participant observation, in-depth interviews, and document analysis, in-depth interviews conducted with two class teachers and one counseling teacher and 8th grade students of SMP Negeri 3 Sragen and documentation. Document analysis will be analyzed thematically. Thematic analysis involves identifying, mapping, and interpreting thematic patterns or motifs that emerge from the data as well as data triangulation, member-checking, and reflective analysis. Based on the results of the author's observation and reflection journal during mathematics learning in class VIII SMP Negeri 3 Sragen, the teacher was seen actively approaching each student individually, providing explanations one by one after the material was presented on the blackboard, guiding students personally in doing guided exercises, and ensuring that each student understood the material individually.